Pengaruh Literasi Keuangan Dan Sikap Keuangan Terhadap Pelaporan Keuangan Pada Umkm Di Kota Medan - Irsan, Muhammad; Sanjaya, Surya; Mustafa, Hartati (Jurnal Riset AKuntansi dan Bisnis, 2025)
The purpose of this study is to determine whether Financial Literacy and Financial Attitude have a significant influence on the Financial Reporting of MSMEs in Medan City, especially in Medan Deli District. This study is a quantitative study with data collection techniques using a questionnaire method given to 48 Micro, Small and Medium Enterprises (MSMEs) in Medan Deli District. The population in this study amounted to 83 MSMEs and the sample in the study amounted to 48 MSMEs. The data analysis techniques used were Outer Model Analysis, Inner Model Analysis, Hypothesis Testing analyzed using Smart PLS software. The results of this study state that Financial Literacy has a significant influence on the Financial Reporting of MSMEs. Then Financial Attitude has a significant influence on the Financial Reporting of MSMEs. And Financial Literacy and Financial Attitude have a significant influence on the Financial Reporting of MSMEs in Medan City, especially in Medan Deli District.